Drug addiction and HIV infection amongst male in Malaysia, 1994 - Juita Ghazalie,; Osman Ali, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Eighty percent of the HIV infected persons in Malaysia are drug addicts. This case control study was conducted amongst drug addicts aged 20-40 years from Rawang Drug Rehabilitation Centre, Selangor in January 1994. The objective of this study is to identify the high-risk behaviour pattern that can help explain the transmission of I HIV among drug addicts. It is hoped that with this information, an appropriate strategy can be formulated in planning the preventive measures for the high-risk group and the public as a whole. The study sample was chosen by stratified random sampling. The cases included 87 HIV seropositives and by frequency matching for age and ethnicity, 261 HIV seronegatives were chosen as the control group. Self-administered questionnaires were circulated to be answered immediately. Findings of this study showed that 59.8 % of the subjects use drugs intravenously of which 71.2% share needles. A total of92.3% of cases share needles as compared to 58.5% from the control group (p < 0.0001). The highrisk behaviors associated with HIV seropositivity were needle-sharing (O.R = 8.53; 95% C.I = 2.10- 6.56), sex with prostitutes (O.R = 3.70; 95% CI = 2.10- 6.56), homosexuality (O.R = 4.05; 95% C.I = 1.49- 11.11) and non-condom use during sex with prostitutes (O.R = 2.27 ; 95% C.I = 1.05 -4.97). When needle-sharing behavior was compared amongst the 3 races, the Malay addicts were found to be 33 times more likely to contract the disease if they shared needi~s a:aici'5 times more at risk if they had Sexual relations with prostitutes as compared to the other races. Analysis also showed that more cases than controls came from broken families (p < 0.05), had disciplinary action taken against them at school (p < 0.05) or were detained by police for various offences committed while still schooling (p < 0.05). The mean age when they started smoking cigarettes was 16.6 :!: 3.4 years and for trying drugs was 20.9 :!: 4.2 years. On the average, more than 50% had used drugs or visited prostitutes or had sexual contacts with their girlfriends by the time they were 20 years old. All drug addicts in me drug treatment and rehabilitation program should not only be adequately informed about HIV/AIDS, but also be motivated to change their high-risk practices so that HIV transmission can be reduced.